EDUKASI KESEHATAN PENYAKIT TIDAK MENULAR PADA PENGUNGSI - Arkianti, Maria Maxmila Yoche; Rumambi, Magda Fiske; Manik, Marisa Juniati; Tompunu, Marianna Rebecca Gadis; Paula, Veronica (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
In the Southeast Asia region, two-thirds of all deaths are due to non-communicable diseases. Half of all premature deaths occur between the ages of 30 and 69 in 2021. The problem of non-communicable diseases can occur in all groups of society. One group at risk includes refugees. While in their home countries, refugees may have limited access to healthcare. As a result, non-communicable diseases may go undetected or poorly managed. Refugees may experience difficult conditions and lack of ongoing care while on the run which can exacerbate non-communicable diseases (NCDs). Indonesia is one of the destination countries for refugees from several countries such as Afghanistan, Myanmar, Somalia, Sudan and Iran. The purpose of this activity is to provide knowledge related to non-communicable diseases to refugees who are at an NGO in Jakarta. This activity was held online with the Zoom application. Education was provided in two sessions. The educational material provided was based on the results of a poll among refugees. Lectures and questions and answers were the methods used in the activity. The event went smoothly with participants showing enthusiasm on the question and answer side. From the evaluation results, participants expected this activity to be held again because the knowledge gained was useful for participants and the health session was very enjoyable.